Prevalence and risk distribution of schistosomiasis among adults in Madagascar: a cross-sectional study - Sarah Katharina Gruninger; Tahinamandranto Rasamoelina; Rivo Andry Rakotoarivelo; Anjarasoa Ravo Razafindrakoto; Zaraniaina Tahiry Rasolojaona; Rodson Morin Rakotozafy; Patrick Richard Soloniaina; Njary Rakotozandrindrainy; Pia Rausche; Cheick Oumar Doumbia; Anna Jaeger; Alexandre Zerbo; et al. (BMC, 2023)
Abstract Background The goal to eliminate the parasitic disease of poverty schistosomiasis as a public health problem is aligned with the 2030 United Nations agenda for sustainable development goals, including universal health coverage (UHC). Current control strategies focus on school-aged children, systematically neglecting adults. We aimed at providing evidence for the need of shifting the paradigm of schistosomiasis control programs from targeted to generalized approaches as key element for both the elimination of schistosomiasis as a public health problem and the promotion of UHC. Methods In a cross-sectional study performed between March 2020 and January 2021 at three primary health care centers in Andina, Tsiroanomandidy and Ankazomborona in Madagascar, we determined prevalence and risk factors for schistosomiasis by a semi-quantitative PCR assay from specimens collected from 1482 adult participants. Univariable and multivariable logistic regression were performed to evaluate odd ratios. Results The highest prevalence of S. mansoni, S. haematobium and co-infection of both species was 59.5%, 61.3% and 3.3%, in Andina and Ankazomborona respectively. Higher prevalence was observed among males (52.4%) and main contributors to the family income (68.1%). Not working as a farmer and higher age were found to be protective factors for infection. Conclusions Our findings provide evidence that adults are a high-risk group for schistosomiasis. Our data suggests that, for ensuring basic health as a human right, current public health strategies for schistosomiasis prevention and control need to be re-addressed towards more context specific, holistic and integrated approaches.